Utilising virtual reality in pain management : a systematic review - Faiz Daud,; Nor Rumaizah MN,; Puteri Sofia Nadira MK,; Mohd Shahir A, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Virtual reality (VR) offers patient with a drug free supplement, an alternative or complementary therapy to traditional pain management. VR technology allowing its use in a wide variety of settings in the medicine world. So, we would like to evaluate the current existing evidence supporting VR in pain management. We conducted a systematic review of interventional and observational studies that examined VR applications in pain management between 2010 and 2019. We used Scopus databases, PubMed, Web of Science, Ovid MEDLINE and EBSCOhost to identify the studies using keywords “patient”, “virtual reality”, “medicine” and “pain management”. Data was obtained by two investigators and agreement was reached with the involvement of a third and fourth investigator. Narrative synthesis for all research was done. A total of 451 citations were identified, among which 12 studies met the criteria for inclusion. Studies involve various countries with participant age ranging from 6 to 75 years old. Studies were small, employed different design, instrument and measure for outcome. Studies addressed experimental, acute and chronic pain with four categories of condition which are burn injury, orthopedic diseases and chronic headache. VR was effective during the procedure in experimental and acute pain management. Majority of studies involving VR in painful physical rehabilitation therapy found VR reduced chronic pain and some provide evidence of lasting analgesia effect of VR after therapy. The usage of VR in chronic pain in term of psychological and cognitive behavioral therapy (CBT) showed improvement of positive mood, emotional and motivation that could lead to improvement of quality of life. VR also useful to elicit findings during painful cervical kinematics assessment in chronic neck pain. VR is a promising technology to be applied in managing chronic and acute pain. Some research showed that VR usage is able to provide lasting effect of analgesia even after VR session. However, there is a need for long term, larger sample sizes and well controlled studies to show clinical and cost-effectiveness for this technology to be used in clinical settings.